2015
DOI: 10.3389/fpls.2015.00895
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of drought response: a tortuous network of transcriptional factors

Abstract: Drought is one of the leading factors responsible for the reduction in crop yield worldwide. Due to climate change, in future, more areas are going to be affected by drought and for prolonged periods. Therefore, understanding the mechanisms underlying the drought response is one of the major scientific concerns for improving crop yield. Plants deploy diverse strategies and mechanisms to respond and tolerate drought stress. Expression of numerous genes is modulated in different plants under drought stress that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
281
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(294 citation statements)
references
References 95 publications
5
281
0
8
Order By: Relevance
“…MYB is the largest TF family regulated by drought stress in both cultivars followed by bHLH and NAC respectively in DT and DS. These TFs might play crucial roles in stress response and our results were consistent with previous studies which indicated that AP2/EREBP, bHLH, bZIP, HD-ZIP, HSF, MYB, NAC, WRKY, and zinc-finger protein TFs had vital roles in the plant response to drought stress (Davey et al, 2009; Mizoi et al, 2012; Sakuraba et al, 2015; Singh and Laxmi, 2015). The heat stress could induce expression of HSFs to protect plants from adverse effects of heat stress (Guo et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…MYB is the largest TF family regulated by drought stress in both cultivars followed by bHLH and NAC respectively in DT and DS. These TFs might play crucial roles in stress response and our results were consistent with previous studies which indicated that AP2/EREBP, bHLH, bZIP, HD-ZIP, HSF, MYB, NAC, WRKY, and zinc-finger protein TFs had vital roles in the plant response to drought stress (Davey et al, 2009; Mizoi et al, 2012; Sakuraba et al, 2015; Singh and Laxmi, 2015). The heat stress could induce expression of HSFs to protect plants from adverse effects of heat stress (Guo et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…WRKY42 involved in negative regulation of transcription. Most of the other up-regulated TF families, such as WRKY, NAC, C2H2, and HSF, participate in drought stress response (Huang et al, 2008; Nishizawa et al, 2008; Sakuraba et al, 2015; Singh and Laxmi, 2015). Particularly, some classes of bHLH TFs were known to bind with CBF genes (DREB1 and 2) under stress conditions and their interaction will contribute to abiotic stress tolerance including drought tolerance (Sreenivasulu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the CBPs, PKs are sensor responders (Batistič and Kudla, 2012) that initiate phosphorylation cascades and thereby play important roles in responses to drought stress (Singh and Laxmi, 2015). The genes of STKs and PKs were upregulated which indicates the initiation of phosphorylation cascades.…”
Section: Discussionmentioning
confidence: 99%
“…According to some reports, ABA promotes JA accumulation (Fan et al 2009). Furthermore, the presence of MYC and NAC transcription factors suggests the existence of cross-talk between JA and ABA signaling (Singh and Laxmi 2015). It should also be noted that ABA and JA antagonistically regulate the expression of salt stressinducible proteins (Moons et al 1997).…”
Section: Signal Transduction Transcription and Translation Processingmentioning
confidence: 99%